A multigrid prolongation relaxation method for solving non-linear equations and its applications. (1st January 2013) - Li, R.L.; Yu, B.; Li, W.
A simple but effective relaxation technique is proposed in multigrid prolongation procedure for solving non-linear equations. The key procedure is relaxing the corrections to be prolonged from coarse to fine grid level. The computational results of two-dimensional convective-diffusion problems indicate that it performs well for both single variable problem solvers and multi-variables coupling problem solvers like SIMPLE algorithm. By applying prolongation relaxation method, the convergence rate improves 21.9 times at most in our calculation.